The “double-edged sword” effect of cytokines in cancer: coexisting opportunities and challenges - Yin, Xuan; Zhang, Wangzheqi; Wang, Guanhua; Liu, Yawei; Dai, Bing; Yue, Liping (Frontiers in Immunology, 2025)
As a key signaling molecule network in the tumor immune microenvironment, cytokines mediate intercellular communication through mechanisms such as autocrine and paracrine, exhibiting a significant “double-edged sword” effect during tumor initiation and progression. The dynamic regulation of this dual effect is influenced by the dependence on concentration, the variability within the tumor immune microenvironment, and the stages of tumor progression, ultimately representing the prolonged co-evolutionary result between tumors and the immune system. Cytokines, as a vital element of the immune microenvironment within tumors, influence cancer promotion by creating intricate networks. Therefore, disrupting this balance to alter the tumor growth environment is of great significance for achieving tumor suppression. In terms of clinical translation, the combined strategy of cytokine therapy and immune checkpoint blockade therapy has significantly improved treatment efficacy by synergistically enhancing immune activation and relieving immune suppression. Meanwhile, approaches such as monoclonal antibodies and bispecific molecules targeting pro-tumor cytokines have provided new insights for overcoming therapeutic resistance. In-depth clarification of the molecular mechanisms underlying the dual effects of cytokines, and breaking through the limitations of single targets from a network perspective, will provide a new paradigm for cancer immunotherapy from basic mechanisms to clinical applications. This will promote the upgrading of targeting strategies towards “dynamic regulation and synergistic intervention,” ultimately improving the prognosis of cancer patients.